2016
DOI: 10.1016/j.jbusres.2016.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stages of economic development on women entrepreneurs' startups

Abstract: Women entrepreneurs add to the economic well-being of countries. This study examines whether stages of economic development (SEDs) influence women entrepreneurs similarly across national settings. This study approaches the environments in which women entrepreneurs launch their businesses from two perspectives-family support and personal problems-in Canada, China, Egypt, Morocco, Poland, South Korea, and Turkey. Findings show that the relationship between SEDs and family instrumental support (financial and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 44 publications
2
47
0
2
Order By: Relevance
“…Research on women entrepreneurship was particularly neglected in the past (Ascher, 2012). However, in recent years, there has been an increasing number of research studies examining women entrepreneurs (Lee & Marvel, 2014;Welsh, Kaciak, & Thongpapanl, 2016). Yadav et al (2016) reviewed 185 papers published in 12 well-established entrepreneurship journals about women entrepreneurship between the 1900s and 2016 and found that this domain was not a significant area of research until late 1990s or even early 2000s.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on women entrepreneurship was particularly neglected in the past (Ascher, 2012). However, in recent years, there has been an increasing number of research studies examining women entrepreneurs (Lee & Marvel, 2014;Welsh, Kaciak, & Thongpapanl, 2016). Yadav et al (2016) reviewed 185 papers published in 12 well-established entrepreneurship journals about women entrepreneurship between the 1900s and 2016 and found that this domain was not a significant area of research until late 1990s or even early 2000s.…”
Section: Literature Reviewmentioning
confidence: 99%
“…they were conducted within some national boundaries (Yadav & Unni, 2016). Therefore, Welsh et al (2016) recommended more quantitative and crosscultural investigations across countries. Minniti et al (2010) highlighted the importance of knowing the differences between and commonalities across individuals and across countries to deepen the understanding of female entrepreneurship (Minniti & Naudé, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 51% of female-owned companies survive more than 10 years, and 61% of female-owned companies are sole proprietorships in Taiwan. Women play a significant role in job creation and economic development (Carrasco, 2014;Welsh, Kaciak, & Thongpapanl, 2016).…”
Section: Introductionmentioning
confidence: 99%